Manajemen public relation dan strategi lembaga pendidikan Islam dalam membangun citra lembaga - Indriani , Irma; Syamsudin, Syamsudin (Indonesian Journal of Educational Management and Leadership, 2023)
The objectives of this research are: 1) to find out the public relation management in building the image of MTs “Andalusia” Boarding School Banjarnegara, 2) to find out the strategy of MTs “Andalusia” Boarding School in building the institution image. The approach used was qualitative and the type of research was descriptive qualitative. The subject of the research was the Leader of the Institution “Andalusia” Banjarnegara, the Headmaster, the employee/ school operator, the teachers/ academic advisors of the classes, the students, the parents/ the guardians of the students, and the people in the environment of MTs “Andalusia” Boarding School Banjarnegara. The data collecting techniques were interview, observation, and documentation. The data analyses used were data reduction, presentation, and conclusion drawing. From the data analyses, the research results are: 1) MTs “Andalusia” Boarding School Banjarnegara has carried out the function of public relation management well even though there has not been the division of public relation in the structure of the organization, 2) The public relation activity is carried out by all civitas academia in MTs “Andalusia” Boarding School Banjarnegara by the management including planning, organizing, implementation, and controlling the public relation activity well, 3) MTs “Andalusia” Boarding School Banjarnegara is building the image of the institution as in the fact by focusing the achievements of the school along with the quality improvement, 4) The efforts of MTs “Andalusia” Boarding School Banjarnegara in building the image of the institution include the activity of the opinion building, the school publication, and the education marketing.